Pelaksanaan Pembiasaan Gerakan Literasi Sekolah di SDN 009 Lubuk Agung - Suslawati, Radani; Dafit, Febrina (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Good literacy skills can help students understand information both verbally and in writing. The implementation of the habituation of the School Literacy Movement is one of the literacy activities and a form of government awareness of the importance of building a literacy culture in the world of education. This study aims to describe the implementation of the habituation of the School Literacy Movement at SDN 009 Lubuk Agung, Kampar Regency. This research is a descriptive qualitative research. The subjects of this study were 1 principal and 6 homeroom teachers. Research instruments in the form of interviews, observations and documentation. The data analysis technique in this study is the presentation of data and drawing conclusions. Based on the results of the study, it shows that the habituation of the School Literacy Movement has not been carried out well, this can be seen from the results of the interviews that reading has not been carried out 15 minutes before the lesson starts, the school facilities and environment are not yet rich in literacy, and also not rich in text, cannot choose reading materials in the classroom. schools, and also not involving the public. From the results of observations based on indicators of habituation of the School Literacy Movement, the implementation of the School Literacy Movement has not been carried out properly.